2019
DOI: 10.12659/ajcr.917973
|View full text |Cite
|
Sign up to set email alerts
|

Successful Depressor Effect Concomitant with Complete Normalization of High Renin and Aldosterone Profile by Percutaneous Transluminal Renal Angioplasty in a Patient with Acute Exacerbated Heart Failure with Preserved Ejection Fraction

Abstract: Unusual or unexpected effect of treatment Background: Although the effect of percutaneous transluminal renal angioplasty (PTRA) on clinical outcomes has not been established in previous clinical studies, some case reports showed that PTRA drastically improved patient outcomes. The appropriateness of PTRA should be discussed in detail. Case Report: A 59-year-old man had been on treatment for hypertension for 5 years, but his blood pressure (BP) had been poorly controlled for the past 5 months. He was hospitaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Although the current expert consensus states that PTRA for ARVD with advanced atrophic kidney and/or chronic total occlusion is rarely appropriate (11), several case studies have reported a positive outcome in such patients (16)(17)(18)(19)(20). In the present case, the occlusive lesion appeared to progress during the time when hypertension had suddenly worsened.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Although the current expert consensus states that PTRA for ARVD with advanced atrophic kidney and/or chronic total occlusion is rarely appropriate (11), several case studies have reported a positive outcome in such patients (16)(17)(18)(19)(20). In the present case, the occlusive lesion appeared to progress during the time when hypertension had suddenly worsened.…”
Section: Discussionmentioning
confidence: 54%
“…Angioplasty was performed four months after the onset of the deterioration of hypertension. In previous case reports as well, angioplasty achieved favorable blood pressure control in patients with advanced atrophic kidney who presented with a sudden deterioration of blood pressure control, and PTRA was performed within six months after the onset of the episode ( 18 , 19 ). When the sudden onset of hypertension or deterioration of blood pressure control leads to the diagnosis of ARVD, the involvement of a stenotic/occlusive lesion is very likely the cause of the blood pressure elevation.…”
Section: Discussionmentioning
confidence: 90%